Fixed Rehabilitation of an ACP PDI Class III Patient - Ana Lucia Machado, DDS, MSc, PhD;1 Larry C. Breeding, MSc, DMD;2 (Journal of Prosthodontics, 2006)
This study evaluated the potential effects of denture base resin water storage time and an effective denture disinfection method (microwave irradiation at 650Wfor 6 minutes) on the torsional bond strength between two hard chairside reline resins (GC Reline and New Truliner) and one heatpolymerizing denture base acrylic resin (Lucitone 199).